Kata Berfrekuensi Tinggi dalam Pembelajaran BIPA Pemula - Esra Nelvi Siagian (Ranah: Jurnal Kajian Bahasa, 2020)
Vocabulary plays an important role in foreign language learning, but teachers are often confused about what vocabulary should be taught or targeted so that learners can communicate well according to their level. This study aims to produce a list of the most frequently used vocabulary, knows as High Frequency Words-HFW, in Beginner Indonesian as Foreign Language (ILF) level. The results of this research will be great used for IFL students, teachers, writers, and observers, as well as parties related to IFL. The use of HFW in foreign language learning is proven to have positive effects, such as increasing learning motivation, increasing self-confidence to produce one's own sentences, helping to understand texts, and using repeated words that will make the vocabulary familiar to learners. This qualitative research used corpus of BIPA books for the beginner level based on the level one and two IFL Competency Standards according to the regulation of education ministry Number 27 of 2017 then processed using the AntCont application. The results showed that 1) HFW for IFL is different from Indonesian HFW in general; 2) the form of word classes taught varies; and 3) limited of affix used.  AbstrakKosakata memegang peranan penting dalam pembelajaran bahasa asing, tetapi pengajar sering bingung menentukan kosakata apa saja yang harus diajarkan atau dijadikan target agar pemelajar dapat berkomunikasi dengan baik sesuai dengan tingkatannya. Penelitian ini bertujuan menghasilkan daftar kosakata yang paling sering digunakan, High Frequency Words-HFW, pada pembelajaran BIPA pemula. Hasil penelitian ini akan sangat bermanfaat bagi para pemelajar, pengajar, penulis, dan pengamat BIPA, serta pihak-pihak yang berkaitan dengan kebipaan. Pemanfaatan HFW dalam pembelajaran bahasa asing terbukti memberi efek positif, seperti meningkatkan motivasi belajar, meningkatkan rasa percaya diri untuk memproduksi kalimat sendiri, membantu memahami teks, dan pemanfaatan kata berulang-ulang akan membuat kosakata tersebut familiar bagi pemelajar. Penelitian kualitatif ini menggunakan korpus data buku-buku BIPA untuk level pemula dengan berbasis Standar Kompetensi Lulusan BIPA level satu dan dua sesuai Permendikbud Nomor 27 Tahun 2017 kemudian diolah menggunakan aplikasi AntCont. Hasil penelitian menunjukkan bahwa 1) HFW bahasa Indonesia untuk pemelajar BIPA berbeda dengan HFW bahasa Indonesia secara umum; 2) bentuk kelas kata yang diajarkan bervariasi; dan 3) bentuk imbuhan yang digunakan terbatas